Forget-Me-Not Lake - Green, Poppy; Bell, Jennifer (Jennifer A.), 1977- (New York : Little Simon, 2015)
Sophie Mouse wants to prove how wonderful mice are for a school project she is doing with her brother, Winston, but starts to have doubts when, even with Hattie and Owen's help, she is unable to learn to swim.
Keywords: Mice -- Fiction; Ability -- Fiction; Swimming -- Fiction; Frogs -- Fiction; Snakes -- Fiction